The concept of individual personality lexicon in modern psycholinguistic studies - Amanbaуeva, G.Yu.; Yushko, N.F. (Ye.A.Buketov Karaganda State University Publishing house, 2014)
The article deals with the question of the definition of «personal lexicon of personality» in modern linguistics. Individual lexicon is a complex of system that is formed under the influence of both linguistic and intralinguistic factors. The article systematizes the definition of individual identity on the basis of a lexicon of modern psycholinguistic theories stand factors influencing its formation in order to identify ways and approaches of studying lexicon. The characteristic of the individual lexicon, in its turn, is the key to unlocking and analysis of individual pictures of the world, helping to find answers to many pressing questions in the study of language phenomena.
Қазіргі заманғы психолингвистикалық зерттеулердегі тілдік тұлғаның жеке лексиконы ұғымы
Понятие индивидуального лексикона личности в современных психолингвистических исследованиях
Keywords: personal lexicon; individual pictures of the world; individual vocabulary; psycholinguistic theories; linguistic identity